Health Problems among School Children: A Community Based Cross-Sectional Study at District Swat Khyber Pakhtunkhwa Pakistan - Naeemullah, Muhammad Jibran Khan, Sara Jamil Khan, Nadia Qazi, Muhammad Iqbal Wahid, Arif Iqbal, Muhammad Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Health status of school children and their school environment plays an important role in the development of physical and mental health, and good personnel behaviors had a significant role in future life of children. Objective: This study was conducted to estimate the frequency of health problems among school children of district Swat, Khyber Pakhtunkhwa Pakistan. Methodology: This study was conducted in district Swat, Khyber Pakhtunkhwa; Pakistan. A total of n=225 school children of age 4-12 years were selected and examined for health problems. A structured questionnaire was used to assess the health status of children regarding health problems. Results: Results showed that 45.56% of children had age < 8 years; 54.44% had age > 8 years; 81.33% of children parents had monthly income < PKR: 45000; 56% children living in mud-made homes; and 46.675 were underweight. Moreover, 15.56% of children had eye discharge; 28.89% backache; 8.44% ear discharge; 16.445 earaches; 47.11% poor oral hygiene status; 60.44% were not using toothbrush; and 22.67% had dental caries. Furthermore, 41.33% had not clean their hair and not took bath within last 48 hours; and 32.89% had poor nail hygiene status for the past one week. Conclusions: It was concluded that school children had several medical health problems and showed relationship with hygiene status of children, tooth-brushing use and its frequency, parents monthly income, and body mass index of children and thus adequate preventive, promotive and behavioral strategies were needed to reduce health problems among school going children. Keywords: School Children, Health Status, Underweight, Eye, Ear, Hygiene, Income, Swat, Kohat